Analisis Faktor-faktor yang Mempengaruhi Kesuksesan Sistem Elektronik PKH Menggunakan Model DeLone dan McLean - Miki Wijana; Utami Aryanti; Sofia Dewi; Nova Indrayana Yusman (Masoem University, 2023)
The PKH electronic system (e-PKH) was created by the Ministry of Social Affairs to improve data accuracy and ensure effective distribution of social assistance. This study aims to analyze the factors that influence the success of e-PKH which are implemented in information systems, in research using the DeLone and McLean Models. This model measure six variable dimensions including system quality, information quality, service quality, use, user satisfaction and net benefits. Data collection techniques were carried out by distributing questionnaires to 217 respondents, while data analysis was carried out using IBM SPSS 23 software. The results showed that system quality, information quality and service quality have a positive and significant effect on use and user satisfaction, usa have a positive and significant effect on user satisfaction, and use and user satisfaction have a positive and significant effect on net benefits.